Severe acute respiratory syndrome (SARS) related coronavirus in bats - Rong Geng; Peng Zhou (BMC, 2021)
Abstract Three major human coronavirus disease outbreaks, severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and 2019 coronavirus disease (COVID-19), occurred in the twenty-first century and were caused by different coronaviruses (CoVs). All these viruses are considered to have originated from bats and transmitted to humans through intermediate hosts. SARS-CoV-1 and SARS-CoV-2, disease agent of COVID-19, shared around 80% genomic similarity, and thus belong to SARS-related CoVs. As a natural reservoir of viruses, bats harbor numerous other SARS-related CoVs that could potentially infect humans around the world, causing SARS or COVID-19 like outbreaks in the future. In this review, we summarized the current knowledge of CoVs on geographical distribution, genetic diversity, cross-species transmission potential and possible pathogenesis in humans, aiming for a better understanding of bat SARS-related CoVs in the context of prevention and control.